Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pengurus Amil Zakat Pondok Pesantren Al-Insan: Yayasan Rumah Harapan Pinus Indonesia - Muhamad Fakhri Abdul Aziz; Sari Marliani; July Yuliawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Employee discipline and performance are fundamental aspects of a company where discipline and poor performance result in the sustainability of the institution. This research aims to analyze the influence of work discipline and work environment on the administrators of the Rumah Harapan Karawang Foundation. This research uses quantitative methods with a descriptive-verification approach, covering all employees of the Rumah Harapan Foundation, and produces a sample of 50 employees. Analysis was carried out using descriptive methods and multiple linear regression. The results of the descriptive analysis show that work discipline (X1), work environment (X2), and employee performance (Y) all meet the